TRANSFORMATION OF ISLAMIC DA'WAH IN THE DIGITAL ERA AND ITS INFLUENCE ON THE RELIGIOUS LITERACY OF MUSLIM MILLENNIALS - A Muwahid Muhammadi; Muammar Zulfiqri; Muhammad Aunurrochim (Karimiyah: Journal of Islamic Literature and Muslim Society, 2026)
The rapid development of digital technology has significantly transformed Islamic da'wah, particularly in the ways religious messages are created, distributed, and consumed. This article examines the transformation of Islamic da'wah in the digital era and its influence on the religious literacy of Muslim millennials, a generation closely connected to digital media. Using a systematic review of empirical and theoretical studies published between 2021 and 2025, the research analyzes how platforms such as YouTube, Instagram, TikTok, and other social media channels have reshaped traditional models of Islamic preaching, religious authority, and communal learning. The findings reveal that digital da'wah has expanded access to Islamic knowledge and increased millennials’ engagement with religious content, contributing positively to religious awareness and worship practices. However, the study also identifies several challenges, including the spread of superficial interpretations, ideological fragmentation, and exposure to radical or decontextualized teachings. The abundance of competing online religious narratives may also create confusion among users in understanding authentic Islamic teachings. The article concludes by proposing the importance of developing critical, moderate, and context-based digital religious literacy to ensure that digital da'wah contributes positively to the intellectual and spiritual development of Muslim millennials.